2020
DOI: 10.1128/cmr.00105-19
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Strategies in Herpes Simplex Virus Encephalitis

Abstract: SUMMARY Herpes simplex virus 1 (HSV-1) can be responsible for life-threatening HSV encephalitis (HSE). The mortality rate of patients with HSE who do not receive antiviral treatment is 70%, with most survivors suffering from permanent neurological sequelae. The use of intravenous acyclovir together with improved diagnostic technologies such as PCR and magnetic resonance imaging has resulted in a reduction in the mortality rate to close to 20%. However, 70% of surviving patients still do not recover complete ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 224 publications
(252 reference statements)
2
57
0
11
Order By: Relevance
“…Herpes simplex virus encephalitis (HSE) caused by HSV-1 infection is the most common sporadic encephalitis worldwide (Piret and Boivin, 2020). DeBiasi et al (2002) found apoptotic neurons and glial cells in the brain tissue sections of patients with acute HSE.…”
Section: Herpes Simplex Virus Encephalitismentioning
confidence: 99%
“…Herpes simplex virus encephalitis (HSE) caused by HSV-1 infection is the most common sporadic encephalitis worldwide (Piret and Boivin, 2020). DeBiasi et al (2002) found apoptotic neurons and glial cells in the brain tissue sections of patients with acute HSE.…”
Section: Herpes Simplex Virus Encephalitismentioning
confidence: 99%
“…Among these, HSVs account for 50 to 75% of viral encephalitis, which consist of brain parenchyma inflammation associated with clinical evidence of neurologic dysfunctions, such as reduced consciousness, behavioral alterations, and impaired cognitive function. 3 The herpetic encephalitis (HSE) is responsible for a high mortality rate between patients who do not receive antiherpetic treatment and for over 70% of neurological sequelae in surviving patients. 3 Given the HSV-1 wide invasive potential of the CNS, it is able not only to agglomerate in the dorsal root nerve ganglia (DRG), but also to migrate to the cerebral cortex itself, including the orbitofrontal, insular, and mesial temporal lobe regions, specially affecting the hippocampus, 4 whose vulnerability to Alzheimer disease is substantial, as demonstrated in pioneer and recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…3 The herpetic encephalitis (HSE) is responsible for a high mortality rate between patients who do not receive antiherpetic treatment and for over 70% of neurological sequelae in surviving patients. 3 Given the HSV-1 wide invasive potential of the CNS, it is able not only to agglomerate in the dorsal root nerve ganglia (DRG), but also to migrate to the cerebral cortex itself, including the orbitofrontal, insular, and mesial temporal lobe regions, specially affecting the hippocampus, 4 whose vulnerability to Alzheimer disease is substantial, as demonstrated in pioneer and recent studies. [5][6][7] Furthermore, evidence carried out with animal models prove that the area analogous to the human limbic cortex is commonly affected by encephalitis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations